A water-responsive calix[4]resorcinarene system: self-assembly and fluorescence modulation - Sosa, María Virginia (2024)
This study explores how water content modulates the self-assembly and fluorescence behavior of two novel calix[4]resorcinarene macrocycles. These macrocycles transition from large, flattened structures in pure THF to large giant vesicles (500-5000 nm) coexisting with small micelles (3.4-3.5 nm) as the water percentage in THF/water mixtures increases up to 53%. At higher water percentages, the assemblies become smaller, forming unimodal micelles with diameters of approximately 140-160 nm. Fluorescence quenching is observed upon water addition, attributed to nonradiative deactivation. These findings highlight water as a key regulator of the assembly and fluorescence of these calix[4]resorcinarene macrocycles, paving the way for further development of water-responsive calixarene systems.